2005
DOI: 10.1007/s10511-005-0003-x
|View full text |Cite
|
Sign up to set email alerts
|

Spots, activity cycles, and differential rotation on cool stars

Abstract: The first results are reported from a search for activity cycles in stars similar to the sun based on modelling their spotting with an algorithm developed at the Crimean Astrophysical Observatory. Of the more than thirty program stars, 10 manifested a cyclical variation in their central latitudes and total starspot area. The observed cycles have durations of 4-15 years, i.e., analogous to the 11 year Schwabe sunspot cycle. Most of the stars have a rough analog of the solar butterfly pattern, with a reduction i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
5
2

Year Published

2005
2005
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 16 publications
4
5
2
Order By: Relevance
“…The R 2 value for the least squares fit for these two periods is quite low (23.6%). It is remarkable that the obtained modulation period is very similar to values often quoted as the long cycle length of LQ Hya (e.g., Jetsu 1993;Oláh et al 2000;Berdyugina et al 2002;Alekseev 2005). However, it is known that given cycle length is nonstationary (e.g., Oláh et al 2011), partially explaining the low quality of the fit in our analysis.…”
Section: Carrier From a Multiperiodic Modelsupporting
confidence: 80%
See 2 more Smart Citations
“…The R 2 value for the least squares fit for these two periods is quite low (23.6%). It is remarkable that the obtained modulation period is very similar to values often quoted as the long cycle length of LQ Hya (e.g., Jetsu 1993;Oláh et al 2000;Berdyugina et al 2002;Alekseev 2005). However, it is known that given cycle length is nonstationary (e.g., Oláh et al 2011), partially explaining the low quality of the fit in our analysis.…”
Section: Carrier From a Multiperiodic Modelsupporting
confidence: 80%
“…These are indeed seen, but with less pronounced phase coherence. Alekseev (2005) also proposed, based on photometric spot modeling, that a latitudinal dynamo wave, the spot activity migrating from the equator poleward (the solar butterfly reversed), is present on the object. The analysis of Lehtinen et al (2012) did not reveal these trends, nor does the CF analysis picture of linear down-or upward trends support this picture.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They used the contemporary Doppler images to identify the latitudes of the spots involved in producing the light modulation and the orbital migration of the phase of light minimum (φ min ) to determine the rotational period. Based on a spot modelling of the photometric data, Alekseev (2005) concluded that spots are confined to only the 30−40 • latitude region, and the active star has a solartype differential rotation; in this case also, the apparent migration of φ min in the orbital phase was used to determine the rotational period. It may be noted that φ min represents the centroid of longitudinal distribution of spots, and any change in the surface distribution will be reflected in its value, hence it is very difficult to derive the rotational period with any great certainty.…”
Section: Discussionmentioning
confidence: 99%
“…Vida et al (2013) studied four systems (one K3, one M4, and the others ∼M1) with very short rotation periods (∼0.45 days) and found similarly short cycles ranging from 0.84 to 1.45 yr in all except the M4. Other nearly-fully convective stars showing signs of a cycle include AD Leo (M3; Buccino et al 2014), GJ375 (M3; Díaz et al 2007), and perhaps EV Lac (M3.5; Alekseev 2005).…”
Section: Introductionmentioning
confidence: 99%